Staphylococcus aureus carriage and contamination of mobile phones among students of An-Najah National University in Palestine - Yosof Al-Masri, Motasem; Abu-Hasan, Nael Sodki (Chulalongkorn Medical Journal, 2020)
Background: Mobile phones have become integral and indispensable accessories. Staphylococcus aureus (S. aureus) nasal and oropharyngeal carriage and mobile phone contamination may represent an important source of cross, auto or nosocomial infections under certain conditions. Objectives: This study aimed to determine the frequency, antibiotic susceptibility, and virulence of S. aureus isolated from the nose and oral cavity and mobile phone contamination among randomly selected students of An-Najah National University in Palestine. Methods: Nasal, oral, and mobile swabs were collected from 300 volunteer students for the isolation of S. aureus. Using disc diffusion test, the susceptibilities of isolated S. aureus strains were determined against erythromycin, oxacillin, vancomycin and clindamycin antibiotics. In addition, clindamycin resistance induction test was conducted. Furthermore, production of virulent factors (gelatinase, protease and/or amylase) by 40 representative S. aureus strains isolated from different sources was determined. Results: The frequency of S. aureus isolation was highest from nasal swabs (30.0%), followed by oral (17.0%) and mobile (7.3%) ones. There were several risk factors that insignificantly increase the frequency of nasal, oral, and/or mobile contamination by S. aureus. Most of the risk factors are related to overcrowding in closed areas, hand contact with common objects, misuse of antibiotics, and improper preparation or preservation of food. Among the 126 isolated S. aureus, resistance was highest against erythromycin (42.1%), followed by oxacillin (15.1%) and clindamycin (9.5%). Remarkably, inducible resistance to clindamycin was found in 30.2% and 12.5% of total and mobile isolates, respectively. The highest frequency of isolation of MRSA was from nasal swabs (17.7%), followed by mobile swabs (12.5%). Similar proportions of production of gelatinase (71.0 - 80.0%) and amylase (62.0 – 71.0%) were found in S. aureus isolated from different sources, but lower frequency of protease production was found in mobile isolates (43.0%) in comparison to oral (85.0%) and nasal (75.0%). Conclusions: A considerable number of students were S. aureus carriers and/or their mobile phones were contaminated with S. aureus. Some isolates were MRSA, with inducible resistance to clindamycim and/or virulent enzyme producers.